Malaysia Economic Monitor, December 2016 : The Quest for Productivity Growth - World Bank Group (World Bank, Kuala Lumpur, 2017)
Malaysia’s economic growth has slowed down but remains resilient to external headwinds. The economic growth rate slowed from 5 percent in 2015 to 4.2 percent, year on year, in the first three quarters of 2016. Private consumption growth slowed down due to a softening labor market and households’ ongoing adjustment to a context of fiscal consolidation. Public investment in infrastructure is offsetting moderation in investment in the oil and gas sector. The gross domestic product (GDP) growth rate is projected to reach 4.2 percent in 2016, with slow improvement moving forward. The fiscal consolidation process remains on track despite lower oil-related revenues. External developments pose the greatest risk to Malaysia’s growth trajectory. Uncertainty regarding the impact of potential US fiscal stimulus policies on global trade, energy prices, financial flows and exchange rates is a major source of external risk, as evidenced with the recent financial outflows from emerging markets and its impact on the value of the ringgit. Bank Negara Malaysia (BNM) has introduced measures to curb ringgit trading in offshore markets while developing and deepening onshore foreign exchange future markets. Continuing good performance on fiscal outcomes, in large part thanks to the introduction of GST, is important in building confidence in the policy framework. This could be supported by further mobilizing and diversifying fiscal revenues, including by broadening the base for the personal income tax and removing some exemptions in the GST. Also, raising efficiency of operational expenditure (i.e. improving the targeting of social assistance) and development expenditures (i.e. greater inter-agency coordination) could provide some additional fiscal space.